GAMBARAN JAMUR PENYEBAB TINEA MANUUM PADA PEKERJA CUCI PIRING RUMAH MAKAN DI WILAYAH SAMARINDA SEBERANG - Nurdiana, Annisa; Sresta Azahra; Nurul Anggrieni (LPPM STIKes Mitra Adiguna, 2024)
Dermatophytosis is a superficial mycosis caused by a fungus. Dermatophytosis is often referred to as tinea infection and is classified according to the part of the body affected. Like tinea manuum which is a dermatophytosis infection on the skin of the palms, back of the hands and fingers. Dishwashing workers tend to be easily infected with the tinea manuum fungus because their working environment is humid and requires them to always be in contact with water. This study aims to determine the description of the fungus that causes tinea manuum in restaurant dishwashing workers in the Samarinda Seberang area. The number of samples in this study involved 35 restaurant workers washing dishes in the Samarinda Seberang area. This type of research is descriptive with a cross sectional research design. The data collected in this study were in the form of primary data and were obtained through direct interviews with the relevant dishwashing workers as well as macroscopic and microscopic laboratory examinations. The results of this study showed that the percentage of respondents' characteristics based on gender was 63% male and 37% female also the percentage of tinea manuum in restaurant dishwashing workers in the Samarinda Seberang Region was 29%. It was concluded that the tinea manuum infection that attacks the dishwashing workers at the Samarinda Seberang area is caused by a dermatophyte fungus, namely Trichophyton sp.